Psychological characteristics of athletes at Pusat Pendidikan dan Latihan Pelajar (PPLP) in Bengkulu - Yahya Eko Nopiyanto; Septian Raibowo; Gilang Ugo Prabowo (Journal Sport Area, 2021)
The study of athletes’ psychological characteristics in the education and students training center (PLPP) Bengkulu needs to be conducted as an effort to fix athletes’ training and achievement in PLPP Bengkulu. The purpose of this study was to determine the psychological difference between male and female athletes in the education and student training center (PPLP) of Bengkulu. Type of this research was quantitative with a comparative design. The subjects in this research were 26 athletes, namely 6 athletic athletes, 4 weight lifting athletes, 8 wrestling athletes, 4 karate athletes, and 4 boxing athletes. The data collection technique was conducted with the psychological skills inventory for sports that adopted from Mahoney, Gabriel & Perkins, (1987). Validity of the instrument is 0,21–0,35 and the reliability is 0,890. Data were analyzed using t-test with a significant level of 0.05. Based on the results of data analysis, it can be seen that male athletes have a mean of 133.52 while female athletes have a mean value of 142.72 and significant value 0f 0,60>0.05. From results of this research, it was concluded that there were no difference in the psychological characteristics between male and female athletes in the education and students training center (PPLP) of Bengkulu. For the next researcher is expected to able using more samples and adding other research variables such as training of psychological skill and athletes personalities.